Outcome of Multilevel Anterior Cervical Discectomy and Fusion without plating - Amanj Dizhwar Khalid; Raqib Seniar Teto (Advanced Medical Journal)
Background & objectives: The safety and efficacy profile of stand-alone polyetheretherketone cages has been questioned in the management of patients with more than one cervical disc disease. In this article, we evaluated the idea of safety of multilevel anterior cervical discectomy and fusion, using a plate and the achieved pain relief.